Economic Essence And Content Of Accounting For Financial Results In Joint-Stock Companies - Azizbek Khurramov (American Journal of Economics and Business Management, 2024)
Financial results are the most important economic indicator that characterizes the results of an organization’s activities and the efficiency of using its resources. It is generally accepted that the financial result is the final result of the organization’s economic activity, which is expressed in the form of profit or loss. Information about the financial results of the organization’s activities, the receipt of profit or loss from financial and economic activities is of interest to all interested users of the information. Thus, tax authorities assess budget revenues; investors - the attractiveness of investing capital in the organization; owners - the quality of production and financial management of the administration; business partners - the success of the organization and the availability of resources to pay off its obligations.